AGROTOURISM AND ITS USE IN KAZAKHSTAN CONDITIONS: INTERNATIONAL EXPERIENCE - A.Temirova,; A.Omarkozhayeva,; S.Yussupova,; I. Yardyakova,; S. Valieva, (Academic Journal of Physical and Chemical Sciences, 2019)
The article discusses the importance and economic importance of agricultural tourism in agriculture, the effectiveness of raising the prestige of rural settlements.